Impact of ATP-citrate lyase catalytic activity and serine 455 phosphorylation on histone acetylation and inflammatory responses in human monocytic THP-1 cells - Dominguez, Monica; Truemper, Verena; Mota, Ana Carolina; Brüne, Bernhard; Namgaladze, Dmitry (Frontiers in Immunology, 2022)
ATP-citrate lyase (ACLY) is a key enzyme provoking metabolic and epigenetic gene regulation. Molecularly, these functions are exerted by the provision of acetyl-coenzyme A, which is then used as a substrate for de novo lipogenesis or as an acetyl-group donor in acetylation reactions. It has been demonstrated that ACLY activity can be positively regulated via phosphorylation at serine 455 by Akt and protein kinase A. Nonetheless, the impact of phosphorylation on ACLY function in human myeloid cells is poorly understood. In this study we reconstituted ACLY knockout human monocytic THP-1 cells with a wild type ACLY as well as catalytically inactive H760A, and phosphorylation-deficient S455A mutants. Using these cell lines, we determined the impact of ACLY activity and phosphorylation on histone acetylation and pro-inflammatory gene expression in response to lipopolysaccharide (LPS). Our results show that ACLY serine 455 phosphorylation does not influence the proper enzymatic function of ACLY, since both, wild type ACLY and phosphorylation-deficient mutant, exhibited increased cell growth and histone acetylation as compared to cells with a loss of ACLY activity. Transcriptome analysis revealed enhanced expression of pro-inflammatory and interferon response genes in ACLY knockout and H760A THP-1 cells under unstimulated or LPS-treated conditions. At the same time, S455A ACLY-expressing cells showed a phenotype very similar to wild type cells. Contrary to ACLY knockout, pharmacological inhibition of ACLY in THP-1 cells or in primary human macrophages does not enhance LPS-triggered pro-inflammatory gene expression. Our data thus suggest that ACLY retains functionality in the absence of Akt/PKA-mediated phosphorylation in human myeloid cells. Furthermore, loss of ACLY activity may elicit long-term adaptive mechanisms, increasing inflammatory responses.